Condition monitoring of overhead line utilising Infrared Thermography (IRT) / Mohd Razif Md Sekak - Md Sekak, Mohd Razif (2004)
The primary objective are to early detection of defect and addressed it before they read to major breakdown. This paper proved that condition monitoring or predictive maintenance is very beneficial compared to preventive maintenance in terms of increasing equipment avaibility and reduced maintenance cost.